Marketing Customer Information File (MCIF): A Powerful Tool for Banks - Sharma, Ashvine Kumar; Nagpal, Shafali (Indian Journal of Marketing, 2006)
With the growing focus on retail business to attract customers and tackle competition, the need for setting up a well-knit marketing function has become crucial for banks. MCIF basically constitutes one of the functions of marketing that provide a strong stimulus to marketing of products and services. It can profile the customer base and assign profitability to accounts, product types, relationships, branches, regions, line divisions and even individual officer’s portfolios. In addition, it can predict seasonal buying habits, identify which customers are most likely to purchase additional product and services, help identify new branch locations, analyze re-pricing and new product opportunities, and much more.